Rights in records: a Charter of Lifelong Rights in Childhood Recordkeeping in Out-of-Home Care for Australian and Indigenous Australian children and care leavers. Issue 9 (21st October 2021) - Golding, Frank; Lewis, Antonina; McKemmish, Sue; Rolan, Gregory; Thorpe, Kirsten
ABSTRACT: This paper introduces the Charter of Lifelong Rights in Childhood Recordkeeping in Out-of-Home Care, centred on the critical, lifelong and diverse information and recordkeeping needs of Australian and Indigenous Australian children and adults who are experiencing, or have experienced Out-of-Home Care. The Charter is underpinned by the findings of two community-centred research projects, the Australian Research Council-funded Rights in Records by Design, 2017–2020 (applying a Rights by Design approach and co-design methodologies to rights-based recordkeeping systems in Out-of-Home Care), and the Indigenous Archiving and Cultural Safety: Examining the role of decolonisation and self-determination in libraries and archives doctoral project, 2018–2020 (focusing on Indigenous self-determination and cultural safety in the context of archives and libraries). It also draws on foundational research on the recordkeeping rights of Indigenous Australians undertaken in the Australian Research Council-funded Trust and Technology project, 2006–2010. The principles and values underpinning the Charter relate to child wellbeing and safety, self-determination, linked to archival autonomy and agency, and Indigenous Sovereignty and cultural safety. The development of the Charter is core to a National Framework for Recordkeeping for Childhood Out-of-Home Care, a major outcome of the 2017 National Summit on Setting the Record Straight for the Rights of the Child .